Relevansi Nilai ‘Ngo Mbeong’ dalam membentuk Etos Kerja Mahasiswa Manggarai di Jayapura - Hironimus Darmawan; fredrik Sokoy; Muhammad Ichsan Rahmanto (CENDERAWASIH: Jurnal Antropologi Papua, 2021)
This article aims to describe and analyze the reasons Manggarai students choose to migrate in Jayapura City and choose to study while working, as well as describe and analyze the influence of cultural values on work ethic in Manggarai students who study while working in Jayapura City. Method used in this research is descriptive qualitative. To obtain objective data, I used observation and in-depth interviews. The data analysis used includes the stages of data reduction, data exposure and data interpretation. The results of this study indicate that Manggarai students who migrate to college while working in Jayapura City have a hard work ethic, discipline, independence, togetherness and mutual help. The formation of their work ethic is influenced by the relevance of cultural values that can form a work ethic. In order to support the needs of daily life and while studying, Manggarai students choose to study while working, the cultural values embedded in them have a strong influence. The cultural values they have are embedded in themselves as a driving force to grow and form a high spirit of work ethic.